Integrated environmental assessment of future energy scenarios based on economic equilibrium models - Elorri Igos; Benedetto Rugani; Sameer Rege; Enrico Benetto; Laurent Drouet; Dan Zachary; Tom Haas (Fondazione Eni Enrico Mattei (FEEM), 2015)
The future evolution of energy supply technologies strongly depends on (and affects) the economic and environmental systems, due to the high dependency of this sector on the availability and cost of fossil fuels, especially on the small regional scale. This paper aims at presenting the modeling system and preliminary results of a research project conducted on the scale of Luxembourg to assess the environmental impact of future energy scenarios for the country, integrating outputs from partial and computable general equilibrium models within hybrid Life Cycle Assessment (LCA) frameworks. The general equilibrium model for Luxembourg, LUXGEM, is used to evaluate the economic impacts of policy decisions and other economic shocks over the time horizon 2006-2030. A techno-economic (partial equilibrium) model for Luxembourg, ETEM, is used instead to compute operation levels of various technologies to meet the demand for energy services at the least cost along the same timeline. The future energy demand and supply are made consistent by coupling ETEM with LUXGEM so as to have the same macro-economic variables and energy shares driving both models. The coupling results are then implemented within a set of Environmentally-Extended Input-Output (EE-IO) models in historical time series to test the feasibility of the integrated framework and then to assess the environmental impacts of the country. Accordingly, a disaggregated energy sector was built with the different ETEM technologies in the EE-IO to allow hybridization with Life Cycle Inventory (LCI) and enrich the process detail. The results show that the environmental impact slightly decreased overall from 2006 to 2009. Most of the impacts come from some imported commodities (natural gas, used to produce electricity, and metalliferous ores and metal scrap). The main energy production technology is the combined-cycle gas turbine plant Twinerg, representing almost 80% of the domestic electricity production in Luxembourg. In the hybrid EE-IO model, this technology contributes to around 7% of the total impact of the country's net consumption. The causes of divergence between ETEM and LUXGEM are also thoroughly investigated to outline possible strategies of modeling improvements for future assessment of environmental impacts using EE-IO. Further analyses focus first on the completion of the models' coupling and its application to the defined scenarios. Once the coupling is consistently accomplished, LUXGEM can compute the IO flows from 2010 to 2030, while the LCI processes in the hybrid system are harmonized with ETEM to represent the future domestic and imported energy technologies.
Keywords: Q40; C61; C67; C68; 330; Life Cycle Assessment; Energy Scenarios; General Equilibrium Model; Techno-economic Model; Environmentally-extended Input-output; Hybridization